Terence M. Ryan (1942-2003): an appreciation - Murphy, Antoin E. (Economic & Social Studies, 2004)
Terence M. Ryan died in June 2003. Terry was one of the most promising members of the nouvelle vague of young Irish economists who studied at the University of Essex in the late 1960s and early 1970s. All had graduated in economics in University College Dublin and went to the campus at Essex to capture the excitement of a younger generation of economists lecturing at graduate level in this renowned new university. Alongside Paddy Geary, Colm McCarthy and Sean Murray he studied under such renowned economists as Chris Archibald, Robert Clower, David Laidler, Richard Lipsey, Michio Morishima and Michael Parkin. The `Essex four? returned to Ireland and all stamped their mark on the development of economic teaching, research and economic policy in Ireland.
Keywords: Obituary; Terence M. Ryan